Parents willingness to pay for a human papillomavirus vaccine to protect their adolescent daughters. Maule Region, Chile. - Arcadio A Cerda; Leidy Y García; Daniela V Albornoz (Instituto Nacional de Salud Pública, 2014)
Objective. To determine the willingness to pay of parents of teenage daughters for a vaccine against human papillomavirus in the Maule Region, Chile. Materials and methods. A sample of 386 parents with daughters between 12 and 18 years old, representing the five largest cities of the Region of Maule, socioeconomically stratified. WTP was obtained using the contingent valuation method in double bounded format. Results. Parents are willing to pay an average of US$ 252.71 to vaccinate their daughters against virus, where the price and number of daughters negatively affects the probability of willingness to pay, and family income positively affects the probability. Conclusion. There is a possibility of using shared funding between the government and the parents of potential daughter to be affected by the human papillomavirus to reduce cervical cancer events.